The Impact of Budget Revenues on the Macroeconomic Stability in Ukraine - BONDARUKІ.; ZNAMENSKYI, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The macroeconomic stability is an important factor in social relations that can occur within the domestic borders. Economic transformations in Ukraine and further development of market-based relations in the volatile business environment require continuous monitoring of macroeconomic dimensions of the economic mechanism at country and regional level. The article’s objective is to present the results of analysis of the public budget revenues and their impact of the macroeconomic stability in Ukraine. The contribution of the public budget as a whole and its revenues in particular to the socio-economic development of a country is highlighted. The essence of the notion “macroeconomic stability” and the nature of the public budget effect for the macroeconomic stability is elaborated on. A detailed analysis of the dynamics of main macroeconomic indicators of Ukraine (public budget revenues, gross domestic product, the structure of economically active population in the working age, unemployment, public debt and publicly guaranteed debt, etc.) over the last decade in made. The analysis of selected macroeconomic indicators shows that Ukraine is a country with macroeconomic instability and low rate of economic recovery. The macroeconomic instability of Ukraine is caused, first and foremost, by the deficit of payment balance and foreign trade, the unfavorable business environment that has adverse effect for the investment attractiveness. The main factors for the economic crisis in Ukraine are ineffective structural reforms, the large shadow segment in the economy, unfair terms of competition, lack of access to the international lending market. Internal risks for the economic development of Ukraine are highlighted.